A clinical assessment and lung tissue burden from an individual who worked as a Libby vermiculite miner. (29th July 2017) - Black, Brad; Dodson, Ronald F.; Bruce, James R.; Poye, Lee W.; Henschke, Claudia; Loewen, Gregory
Abstract: During its days of operation (1920s–1990), the world's largest source of vermiculite was extracted from a mine located near Libby, Montana. The material mined at this site was shipped for various commercial applications to numerous sites in the United States. There was a "fibrous" component with toxic potential within the vermiculite deposit that has resulted in "asbestos-like" diseases/deaths being reported in numerous studies involving miners as well as residents of the town of Libby. The present case involves the clinical assessments of an individual who worked at the mine from 1969 to 1990. He had no other known occupational exposures to fibrous materials. He developed a clinical picture that included "asbestos-like" pathological features and eventually an adenocarcinoma. The clinical assessment including radiographic features will be presented. The evaluation will also include the analytical evaluation of the fibrous/ferruginous body composition of the lung tissue. This is to our knowledge the first time such an extensive evaluation has been conducted in a vermiculite miner from Libby, Montana.